2005
DOI: 10.1021/jm040889k
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Pharmacological Characterization of trans-2-Amino-5(6)-fluoro-6(5)-hydroxy-1-phenyl-2,3-dihydro-1H-indenes as D2-like Dopamine Receptor Agonists

Abstract: The present work reports the synthesis of trans-2-amino-5(6)-fluoro-6(5)-hydroxy-1-phenyl-2,3-dihydro-1H-indenes (4a-f, 5a-f) as a continuation of our studies to better understand the significance of the halo substituent in the trans-1-phenyl-2-aminoindane series and to extend knowledge of the monophenolic ligands of DA receptors. The affinity of the new compounds and related methoxylated precursors (10-15 and 18-23) was estimated in vitro by displacement of [(3)H]SCH23390 (for D(1)-like receptors) or [(3)H]YM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 21 publications
12
22
0
Order By: Relevance
“…For instance, we found that electrical and chemical stimulation of the substantia nigra (SN) and systemic DA D 1 receptor agonist administration both robustly increase striatal NO efflux via nNOS and DA D 1 receptor-dependent mechanisms (Sammut et al 2006). In agreement with our study, DA D 1 receptor activation has been shown to increase striatal tissue levels of the NO second messenger cGMP (Altar et al 1990;Di Stefano et al 2005;Siuciak et al 2006b). Conversely, DA D 2 receptor activation decreases striatal tissue levels of cGMP (Di Stefano et al 2005).…”
Section: Abbreviationssupporting
confidence: 88%
“…For instance, we found that electrical and chemical stimulation of the substantia nigra (SN) and systemic DA D 1 receptor agonist administration both robustly increase striatal NO efflux via nNOS and DA D 1 receptor-dependent mechanisms (Sammut et al 2006). In agreement with our study, DA D 1 receptor activation has been shown to increase striatal tissue levels of the NO second messenger cGMP (Altar et al 1990;Di Stefano et al 2005;Siuciak et al 2006b). Conversely, DA D 2 receptor activation decreases striatal tissue levels of cGMP (Di Stefano et al 2005).…”
Section: Abbreviationssupporting
confidence: 88%
“…Remarkably consistent outcomes have been reported in studies examining the impact of DA D1 and D2-like receptor agonists/ antagonists on striatal NOS activity and NO production via cGMP (Di Stefano et al, 2005;Sammut et al, 2006;Siuciak et al, 2006;Park and West, 2009;Hoque et al, 2010).…”
Section: Discussionsupporting
confidence: 76%
“…Striatal elevation of cGMP is another common feature of D2 antagonists (Altar et al, 1990;Di Stefano et al, 2005), PDE10A inhibitors , and PDE9A inhibitors. However, in contrast to antipsychotics and PDE10A inhibitors, the PDE9A inhibitors did not affect spontaneous or stimulant-induced locomotor activity or conditioned avoidance responding.…”
Section: Downloaded Frommentioning
confidence: 99%